Análisis de anualidades de préstamos para los proyectos de inversión. - Chuchuca Arévalo, Irma Adolfina (My University, 2019)
The alternatives presented by the financial system when considering financing for productive processes and investment, undoubtedly the country's finance sector provides savers with the channeling of their savings towards investment, benefiting society and companies accessing system resources financial to finance your individual or business needs. It is worth mentioning when financing is made, the so-called annual payments or periodic payments that investors make with the purpose that the interest benefits them with income. In the same way, those who acquire loans must pay the financial institutions periodic payments that are also known as annuities that include interest for the amount granted.
Las alternativas que presenta el sistema financiero al momento de considerar un financiamiento para procesos productivos e inversión, sin duda el sector de finanzas del país brinda a los ahorristas la canalización de sus ahorros hacia la inversión beneficiando a la sociedad y empresas accedan a recursos del sistema financiero para financiar sus necesidades individuales o empresariales. Cabe mencionar cuando se realiza un financiamiento aparecen las denominadas anualidades o pagos periódicos que hacen los inversionistas con la finalidad que el interés los beneficie con ingresos. De la misma forma quienes adquieren préstamos, deben abonar a las instituciones financieras pagos periódicos que también se conoce como anualidades que incluyen intereses por el monto concedido.
Keywords: ANUALIDADES; FINANCIAMIENTO; INVERSIÓN; INTERÉS